Psychological science on pregnancy stress processes, biopsychosocial models, and emerging research issues. [article]. - Schetter, Christine Dunkel
Psychological science on pregnancy is advancing rapidly. A major focus concerns stress processes in pregnancy and effects on preterm birth and low birth weight. The current evidence points to pregnancy anxiety as a key risk factor in the etiology of preterm birth, and chronic stress and depression in the etiology of low birth weight. Evidence regarding social support and birth weight is also reviewed with attention to research gaps regarding mechanisms, partner relationships, and cultural influences. The neurodevelopmental consequences of prenatal stress are highlighted, and resilience resources among pregnancy women are conceptualized. Finally, a multilevel theoretical approach for the study of pregnancy anxiety and preterm birth is presented to stimulate future research.- (from the author)
Keywords: Preterm birth; Low birth weight; Pregnancy anxiety; Prenatal stress; Social support; Coping and resilience